Ethnotherapeutic Profile of Medicinal Plants Used during Postnatal Recovery (Postpartum) in South Eastern Nigeria: A Review - V. Adaku Iwueke; C. Ezinne Chukwu (Archives of Current Research International, 2020)
Plant derived bioactive constituent has lead credence to usage of medicinal plants namely spices in postnatal recovery in most cultures especially in South Eastern Nigeria. Postpartum is a critical phase leading to recovery for the nursing mother and improved health condition for the new born. Most of these medicinal plants play important role and are used as diet therapy after childbirth to induce contraction of the uterus, energy induction and improve production of breast milk. A systematic and comprehensive review of these medicinal plants for holistic utilization is pertinent. Therefore, this review validates and highlights the health benefits of medicinal plants used during postpartum period in South Eastern Nigeria.